Measuring psychosocial outcomes of men living with prostate cancer: feasibility of regular assessment of patient‐reported outcomes. (26th December 2020) - Ettridge, Kerry; Wright, Kathleen; Smith, David; Chambers, Suzanne; Corsini, Nadia; Evans, Susan; Moretti, Kim; Roder, David; Scuffham, Paul; Miller, Caroline
Abstract: Objective: To trial collecting patient‐reported outcome measures (PROMs) to assess psychosocial outcomes in men with prostate cancer (PC). Methods: A cross‐sectional postal survey was sent to three groups of 160 men with PC (6, 12 and 24 months post‐initial treatment; n total = 480), through the South Australian Prostate Cancer Clinical Outcomes Collaborative (SAPCCOC) registry (2017). Outcomes were as follows: response rate, completeness, general and disease‐specific quality of life, distress, insomnia, fear of recurrence, decisional difficulties and unmet need. Results: A response rate of 57–61% ( n = 284) was achieved across groups. Data completeness was over 90% for 88% of survey items, with lower response (76–78%) for EPIC‐26 urinary and sexual functioning subscales, sexual aid use (78%) and physical activity (68%). In general, higher socio‐economic indicators were associated with higher completion of these measures (absolute difference 12–26%, p < 0.05). Lower unmet need on the sexuality domain (SCNS‐SF34) was associated with lower completion of the EPIC‐26 sexual functioning subscale [M (SD) = 12.4 (21.6); M (SD) = 26.3 (27.3), p < .001]. Worse leaking urine was associated with lower completion of urinary pad/diaper use question (EPIC‐26) [M (SD) = 65.9 (26.5), M (SD) = 77.3 (23.9), p < .01]. Conclusion: Assessment of psychosocial PROMs through a PC registry is feasible and offers insight beyond global quality of life assessment, to facilitate targeting and improvements in services and treatments.